Monitoring COVID-19 Impacts on Households in Ethiopia : Results from a High-Frequency Phone Survey of Households - Wieser, Christina (World Bank, Washington, DC, 2020)
The COVID-19 pandemic and its economic and social effects on households have created an urgent need for timely data to help monitor and mitigate the social and economic impacts of the crisis and protect the welfare of the least well-off in Ethiopian society. To monitor how the COVID-19 pandemic is affecting Ethiopia’s economy and people and to inform interventions and policy responses, the World Bank designed and conducted its High-Frequency Phone Survey of Households (HFPS-HH).